HLA-DPB1*04:01 allele is associated with non-obstructive azoospermia in Japanese patients - Timothy Adrian, Jinam; Hirofumi, Nakaoka; Kazuyoshi, Hosomichi; Shigeki, Mitsunaga; Hiroyuki, Okada; Atsushi, Tanaka; Kenichi, Tanaka; Ituro, Inoue (Springer Nature, 2013)
Azoospermia is defined by absence of sperm in the semen and can either be caused by obstruction of the seminal tract (obstructive azoospermia) or by defects in spermatogenesis (non-obstructive azoospermia, NOA). Previous studies reported that specific alleles and single nucleotide polymorphisms (SNPs) in the human leukocyte antigen (HLA) region were associated with NOA in East Asians. We attempt to expand upon previous findings by genotyping more HLA genes and to replicate SNP associations by focusing on Japanese NOA patients. HLA typing of six genes (HLA-A, -B, -C, -DRB1, -DQB1, and -DPB1) was done on 355 NOA patients using SSO-Luminex assay while genotyping of two previously reported SNPs (rs498422 and rs3129878) was done on 443 patients and 544 fertile males using TaqMan assay. Association was assessed with Chi squared and logistic regression tests. We found that HLA-DPB1*04:01 [corrected p value, Pc 7.13 9 10-6 ; odds ratio (OR) 2.52], DRB1*13:02 (Pc 4.93 9 10-4 , OR 1.97), DQB1*06:04 (Pc 8.94 9 10-4 , OR 1.91) and rs3129878 (p value 3.98 9 10-4 ; OR 1.32) showed significant association with NOA, however, these loci are in linkage disequilibrium with each other. The conditional logistic regression tests showed that DPB1*04:01 is independently associated with NOA, confirming the involvement of the HLA region in the etiology of NOA in Japanese patients.